EVALUASI PENGARUH GEOMETRI JALAN ANGKUT OVERBURDEN TERHADAP PRODUKSI OHT CATERPILLAR 777D DARI PIT 1 UTARA LOADING POINT CE 7139 MENUJU IPD 1 N, PT. ADIMITRA BARATAMA NUSANTARA, SANGA-SANGA, KUTAI KARTANEGARA, KALIMANTAN TIMUR - Yoszi Mingsi Anaperta; Muhammad Ikmal (Universitas Negeri Padang, 2018)
Overburden removal from north pit 1 at PT. Adimitra Baratama Nusantara has a production target of April 2018 of 295.044 BCM while the actual production isonly 189.808 BCM. The combination of units in this location are 1 unit of excavator CATERPILLAR 6030 and 4 units of OHT CATERPILLAR 777D. Not The achievement of production monthly be foundation author research. In conducting this problem research, the authors combine the theory with field data, so that both of them obtained a problem solving approach. Evaluation of road geometry is needed to determine the rimpull in order to get a calculation of cycle time estimation and the production of hauler after road repair. Based on the calculation of the road geometry evaluation, the minimum width of each straight and bend road must beapplied are 21,5 meters and 22 meters. Grade > 10% must bereduced to 10% whichis the grade tolerance limit that OHT could pass. Superelevation of the bend that must be made is121,65 cm and the cross slopet hat must be applied is 43 cm. The actual production achieved is 287.789,75 BCM while the estimated increase in production after road repair is 377.925,6 BCM